Feminist strategies for changing the story: re-imagining Arctic exploration narratives through (the staging of) photographs, travel writing and found objects - von Spreter, Stephanie (Journal of Aesthetics & Culture, 2021)
This article shows how contemporary artistic practice seeks to re-evaluate, re-interpret and re-imagine (historical) Arctic exploration narratives that have generally been considered gendered and dominated by men. It particularly examines the work of contemporary Norwegian artist Tonje Bøe Birkeland, whose entire practice emerges from embodying and staging imagined turn of the century woman explorers. One of Birkeland’s explorers travels to the Arctic and the circumpolar North and explicitly references persisting narratives deriving from the so-called heroic era of polar exploration. In order to change these narratives, I argue, Birkeland employs two feminist strategies: firstly, by storytelling and speculative fabulation (Haraway); secondly, by simultaneously complying with and disrupting re-occurring Arctic motifs and representations. Photography, travel writing and found objects are hereby her primary artistic mediums and “accomplices” in fulfilling these strategies, carefully orchestrated in a photobook in order to establish her story and view on the Arctic world. As a result, Birkeland not only reveals which stories about the Arctic are missing and could have been told. She also asks us to imagine how our relationship to the Arctic could have been shaped differently and how, through this process, it is possible to influence a future narrative of a (still) gendered Arctic.